Financial and economic analysis of energy relations between Turkey and Azerbaijan - Ekici, Mehmet Sena; Arpa, Abdullah Taha (Rating Academy, 2021)
Energy, which is one of the important issues of economy and public finance, is an essential need for human life from past to present. Energy, which finds use in almost most areas of human life, continues its current role and field diversity by increasing day by day. Countries that have this resource gain significant advantages due to the richness of raw materials. Within the framework of international policy, countries that have energy resources achieve significant gains at the international level. Although Turkey is not yet reached the required reserves in the field of energy supply security on the basis of the reserve resources to carry through with economic disadvantages reserves by road is turning effort to benefit in this way. It has developed various projects with neighboring geographies in order to supply the amount of supply needed in the face of intense energy consumption within the country’s territory at low cost and in sustainable ways. And these projects have paid off through pipelines. Turkey is the owner of the land owned by geopolitical advantage. As a result of the strategies it carries out to make use of this advantage, it assumes a corridor position in the field of Energy. security of energy supply in the international arena is relatively behalf of the continuity of their neighbors in Turkey for stability in a country that is more suited to the role of trust to be safe corridor between exporting and importing countries on the issue. In recent years, with the activation of the Tanap and Trans Adriatic lines, a significant momentum has been achieved in this area. Turkey’s dependence on Russia in the energy field within the framework of the realization of common interests between the two states, one nation watchword Turkey and Azerbaijan have decreased significantly. Especially in the last two years, exploration and scanning activities in the Eastern Mediterranean have started to yield results and promising developments have been achieved in terms of natural gas reserves.

Iktisadin ve Kamu maliyesinin önemli konularindan biri olan enerji, geçmisten bugüne insan hayati için elzem bir ihtiyaçtir. Insan hayatinin hemen hemen çogu alaninda kullanim alani bulan enerji, mevcut rolünü ve alan çesitliligini, her geçen gün arttirarak sürdürmektedir. Söz konusu kaynaga sahip olan ülkeler, hammadde zenginligi sebebiyle önemli avantajlar elde etmektedir. Uluslararasi politika çerçevesinde, enerji kaynagina sahip olan ülkeler, uluslararasi düzeyde önemli kazanimlar elde etmektedir. Türkiye ise henüz enerji alaninda istenilen rezervlere ulasamamis olmasina ragmen rezerv kaynaklarin arz güvenligi temelinde ekonomik yollarla tasinmasina aracilik ederek rezerv dezavantajini bu yolla avantaja çevirme gayretindedir. Ülke topraklari içerisinde yogun enerji tüketiminin karsisinda ihtiyaç duyulan arz miktarini düsük maliyetle ve sürdürülebilir yollarla temin edebilmek için komsu cografyalarla çesitli projeler gelistirmistir. Ve bu projeler boru hatlari vasitasiyla meyvesini vermistir. Türkiye sahip oldugu topraklar ile jeopolitik açidan avantaj sahibidir. Bu avantajini degerlendirmek adina yürüttügü stratejiler neticesinde enerji alaninda koridor pozisyonu üstlenmektedir. Türkiye bölgesindeki istikrarin sürekliligi adina komsularina nispeten uluslararasi sahada daha fazla güven veren bir ülke konumunda oldugu için enerji arz güvenligi hususunda ihracatçi ve ithalatçi ülkeler arasinda güvenli koridor olma rolüne uygundur. Son yillarda TANAP ve Trans Adriyatik hattinin faaliyete geçirilmesiyle bu alanda önemli bir ivme yakalanmistir. Türkiye ve Azerbaycan arasindaki iki devlet tek millet düsturunun ortak menfaatler çerçevesinde gerçeklestirilmesi ile Türkiye’nin enerji alaninda Rusya’ya olan bagimliligi da önemli oranda azalmistir. Özellikle son iki yilda Dogu Akdeniz’de gerçeklestirilen arama ve tarama faaliyetleri netice vermeye baslamis ve dogalgaz rezervleri anlaminda umut verici gelismeler saglanmistir. Bu çalismanin amaci Türkiye ve Azerbaycan ülkeleri arasindaki enerji iliskilerini hem iktisadi hem de mali açidan irdelemektir.
Türkiye ve Azerbaycan arasindaki enerji iliskilerinin mali ve iktisadi analizi
Keywords: Economics; Ekonomi